MANAJEMEN STRATEGI TOL BALI MANDARA DI MASA PANDEMI COVID19 - Sugi Kurnia Dewi, Putu (Jurnal TAMBORA, 2020)
The Covid-19 pandemic, which began in March 2020 until now, has an impact ondecrease in the number of vehicles using the Bali Mandara Toll Road. amountabout 80% less than usual. This certainly has an impacton Bali Mandara Toll revenues. Therefore, it is necessary to study the management of the Bali Toll RoadMandara during the Covid-19 period. Data and information obtained from observations,documentation, and interviews. Furthermore, strategic management analysis is carried outqualitative. From the analysis, two strategies are suggested, namely the functional strategycompany and generic strategy. It is hoped that these two strategies will helpthe manager of the Bali Mandara Toll Road facing the Covid-19 Pandemic.